2001
DOI: 10.1128/iai.69.9.5494-5501.2001
|View full text |Cite
|
Sign up to set email alerts
|

Novel Extracellular x-Prolyl Dipeptidyl-Peptidase (DPP) from Streptococcus gordonii FSS2: an Emerging Subfamily of Viridans Streptococcal x-Prolyl DPPs

Abstract: Streptococcus gordonii is generally considered a benign inhabitant of the oral microflora, and yet it is a primary etiological agent in the development of subacute bacterial endocarditis (SBE), an inflammatory state that propagates thrombus formation and tissue damage on the surface of heart valves. Strain FSS2 produced several extracellular aminopeptidase and fibrinogen-degrading activities during growth in culture. In this report we describe the purification, characterization, and cloning of a serine class d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 54 publications
(45 reference statements)
2
32
0
1
Order By: Relevance
“…To a lesser extent, other dipeptides, including Lys-Ala-pNa, Arg-Pro-pNa, Ala-Ala-pNa, and Asp-Pro-pNa, were also hydrolyzed by the protease. A similar observation was previously reported for other bacterial DPP IVs (2,7,17,25).…”
Section: S Suissupporting
confidence: 75%
See 1 more Smart Citation
“…To a lesser extent, other dipeptides, including Lys-Ala-pNa, Arg-Pro-pNa, Ala-Ala-pNa, and Asp-Pro-pNa, were also hydrolyzed by the protease. A similar observation was previously reported for other bacterial DPP IVs (2,7,17,25).…”
Section: S Suissupporting
confidence: 75%
“…The deduced amino acid sequence from the nucleotide sequence revealed that it contained a complete open reading frame coding for a 755-aminoacid protein with a calculated molecular mass of 85 kDa. This correlates well with the molecular masses previously reported for other DPP IVs, including those from P. albensis (27), S. gordonii (7), Lactobacillus sakei (20), and S. thermophilus (25).…”
supporting
confidence: 75%
“…21) Therefore, short-chain fatty acids can be expected to be a therapeutic alternative for IBD patients by stimulating renewal of the injured epithelium. Homologues of the Dppiv gene have also been found in several bacteria, including Lactobacillus helveticus, 22) Streptococcus gordonii, 23) and Porphyromonas gingivalis. 24) Porphyromonas gingivalis invades connective tissue and attaches to the extracellular matrix because of the interaction between fibronectin and DPPIV.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these carry the LPxTz motif for covalent cell wall anchorage, and some do not and are released into the environment (Tables 1 and 2). A dipeptidase from S. gordonii is secreted and released but carries no signal peptide (195). Clearly, there is still a limited understanding of the molecular mechanisms of protein secretion in streptococci.…”
Section: Ig-binding Proteinsmentioning
confidence: 99%